Baseflow recession of some selected rivers in Peninsular Malaysia - Lai, Food See (Institusi Jurutera Malaysia, 1987)

(untitled)
This paper examines the baseftow recession curves for 4 rivers in a western section of Peninsular Malaysia. Mean daily discharge data were used in determining the hydrograph of baseflow. Two approaches, enveloping and statistical regression were used in determining the daily depletion factor, K.From the analysis, K derived by enveloping and statistically, differ by 0.9 to 5.9% for the rivers using both methods. In addition, slight differences between baseflow recession constant value were noted for 2 characteristic dry periods which is typical in this part of the country.